Beyond Digital Literacy: A Qualitative Inquiry into AI Readiness and Dynamic Capabilities of Micro Enterprises in North Sulawesi - Taroreh, Stefen Raymundo Agustinus; Mandalika, Wahyu; Wasilu, Irfan; Pratama, Risky; Wahyuningsih, Wahyuningsih (Journal of Literacy and Education, 2025)
The rapid spread of Generative Artificial Intelligence (GenAI) enables resource constrained businesses to leapfrog traditional development stages. However, current literature predominantly focuses on digital literacy and adoption intentions, often overlooking the strategic utilization of AI in peripheral tourism economies. This study aims to explore how micro enterprises in Bunaken, North Sulawesi, leverage AI tools to build dynamic capabilities beyond basic technical skills. Employing a qualitative descriptive design, this study investigates the lived experiences of 12 tourism based micro entrepreneurs. Data were collected through in depth semi structured interviews and digital observations. The study utilizes the Dynamic Capabilities View (DCV), specifically sensing, seizing, and transforming as the theoretical lens to analyze how participants integrate tools like ChatGPT and Gemini into their daily operations. The results reveal that AI readiness in this context is best characterized as "Pragmatic Bricolage" rather than formal technical proficiency. Participants exhibit a distinct dichotomy in tool usage: ChatGPT is leveraged for creative content generation and cultural translation (seizing capabilities), while Gemini is utilized for real time market intelligence and information verification (sensing capabilities). The study identifies that GenAI acts as a cost effective mechanism for "frugal innovation," effectively bridging the language and resource gaps inherent in the region, though usage is tempered by the need for "human in the loop" verification to mitigate AI hallucinations. This research contributes to the digital entrepreneurship literature by providing empirical evidence from an underrepresented archipelago context. It theoretically extends the DCV framework by proposing that in micro enterprises, dynamic capabilities can be constructed through accessible AI tools, shifting the focus from "digital literacy" to "AI enabled strategic agility".